1996
DOI: 10.1007/s004390050234
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the human apolipoprotein-J/clusterin gene: ethnic variation and distribution in Alzheimer's disease

Abstract: Apolipoprotein-J/clusterin (APOJ/CLI) shares many biological properties with apolipoprotein-E (APOE) including, but not limited to, avid binding with beta-amyloid peptide. Thus, APOJ/CLI warrants scrutiny as a candidate Alzheimer's disease (AD) susceptibility gene. We identified seven nucleotide sequence polymorphisms in APOJ/ CLI, two of which, in exon 7, after the predicted amino acid sequence. The JVIIB variant is an asparagine-to-histidine substitution, which deletes a glycosylation signal at amino acid 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 35 publications
(29 reference statements)
2
35
1
2
Order By: Relevance
“…Hispanics from this country and other Caribbean nations may share some of their genetic background with individuals of African descent, which may partially explain the similarity in disease risk. [64][65][66] Because the proportion of African-American and Hispanic individuals living beyond age 65 years in the United States is increasing more rapidly than the proportion of white individuals, 67 it is imperative that this disparity in the rates of disease among the elderly be understood.…”
mentioning
confidence: 99%
“…Hispanics from this country and other Caribbean nations may share some of their genetic background with individuals of African descent, which may partially explain the similarity in disease risk. [64][65][66] Because the proportion of African-American and Hispanic individuals living beyond age 65 years in the United States is increasing more rapidly than the proportion of white individuals, 67 it is imperative that this disparity in the rates of disease among the elderly be understood.…”
mentioning
confidence: 99%
“…Seven variants were discovered within the gene, including two non-synonymous changes, but none showed association with the disease in their sample set (Tycko et al 1996).…”
Section: Clumentioning
confidence: 99%
“…Nine exons of the APOJ gene were divided into 4 sets and screened for genetic variants using heteroduplex analysis and single-strand conformation polymorphism (SSCP) with designated paired primers as previously published [20,25]. The primer sequences were as follows: exon 1(F) TCCGCGGCATTCTTTGGGC and exon 1(R) TGCCCGCCCATCCGTCCTG which generated a 210-bp product; exon 2(F): CGTGCAAAGACTCCAGAA and exon 2(R) TGGCCAGAGGAACATCAT which generated a 156-bp product; exon 3(F) CTCTTGCACTTCTCTTGC and exon 3(R) TCCAGTGGGATGGTCAAG which generated a 216-bp product; exon 4(F) AGCCTTGTGTCTTCCTGT and exon 4(R) GCATATTTCACTAGGCTC which generated a 258-bp product; exon 5(F) GAGCTTCTCCTAACTGTG and exon 5(R) AAAGGCCATGAGCTTCCA which generated a 478-bp product; exon 6(F) CTGGATGACTGACACTTC and exon 6(R) TCCATAAAGGCAGCACCA which generated a 229-bp product; exon 7(F) CTTCCCTTCACACTTCTC and exon 7(R) GACTTTAGCAGCTCGTTG which generated a 151-bp product; exon 8(F) CCACAGTGTTTCAGCTCT and exon 8(R) TTTTGTGGCTCCCAGAGA which generated a 278-bp product; exon 9(F) GGATGTTTTACTTTGGAGG and exon 9(R) AGAGGCTGGGCGGAGTTGG which generated a 190-bp product.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have investigated polymorphisms in the LCAT gene [18], the gene-encoding lipoprotein lipase [19] and in the APOJ gene [20,21,22,23]. A study that enrolled Japanese female patients reported a relationship between a polymorphism of the APOJ gene and atherosclerosis [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation